Irrigation management impacts on cotton reproductive development and boll distribution. Issue 4 (9th July 2022) - Herritt, Matthew T.; Thompson, Alison; Thorp, Kelly
Abstract: Cotton ( Gossypium hirsutum L.) reproductive development is affected by irrigation management and reduced soil moisture, leading to yield impacts. This study was conducted to determine how irrigation timing and reduced soil moisture affects the distribution of cotton reproductive structures throughout the canopy. Reduced soil moisture was achieved through varied irrigation amounts based on recommendations from an agroecosystem model. Plants from each irrigation treatment were destructively sampled bi‐weekly and squares, green bolls, and abscissions were counted on mainstem fruiting branches. Plant height, leaf area, and dry weights of squares, flowers, and green bolls were measured. Reduced irrigation from first square to peak bloom reduced the number of green bolls in the lower middle quarter of mainstem nodes, where most bolls are located. Reproductive development and growth were most sensitive to reduced soil moisture treatments and irrigation rates from squaring to peak bloom, whereas the period from peak bloom to 90% open boll was unaffected by irrigation rates. Core Ideas: A 60% irrigation rate from squaring to 90% open boll was most impactful on growth and development. Reduced irrigation impacted the middle of plant canopy, which reduced fiber yield. Management can avoid these losses with 20% irrigation savings from square to peak bloom.